Morphometric Variations in Cassava ( Manihot esculenta Crantz) Whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) from different Agro-Ecological Zones of Kerala, India - Harish, E R; Chellappan, Mani; Makesh Kumar, T; Ranjith, M T; Ambavane, A R (JOURNAL OF ROOT CROPS, 2017)
The silverleaf whitefly, Bemisia tabaci, is the main limiting factor in the production of one of the most important tuber crops in the world, cassava. The cassava mosaic virus transmitted by the insect causes cassava mosaic disease and it accounts for about 40% reduction in the tuber yield. The present study evaluates the presence of different genetic groups, using morphometric variations among whitefly populations collected from all agro-ecological zones of Kerala, India. Studying fourteen different pupal characters and nine different adult characters could not establish significant variations in most of the characters studied, between these agro-ecological zones. But, the principal component analysis revealed the presence of more variations in populations collected from Sulthan Bathery compared to others. Further molecular studies using the populations could provide a clear cut idea about the presence of different genetic groups/ biotypes in these regions.